2019
DOI: 10.3389/fimmu.2019.02532
|View full text |Cite
|
Sign up to set email alerts
|

Biology of IL-36 Signaling and Its Role in Systemic Inflammatory Diseases

Abstract: Interleukin (IL)-36 is a member of the IL-1 superfamily and includes three agonists (IL-36α, IL-36β, and IL-36γ) and an antagonist (IL-36Ra). IL-36 agonists bind to heterodimeric receptor complexes. Then, the heterotrimer complexes signal via intracellular functional domains, binding to downstream signaling proteins and inducing inflammatory responses. In this review, we summarized the current knowledge about the biological role of IL-36 and its correlation with systemic inflammatory diseases. The information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 56 publications
(87 reference statements)
0
67
0
Order By: Relevance
“…Table S1 lists the Top 50 differentially upregulated genes in OPM of VEH-untreated SIV rhesus macaques. Notable genes that were significantly upregulated exclusively in OPM of VEH-untreated/SIV rhesus macaques ( Figure 1 A) included IL1RN (inhibits activity of interleukin-1) [ 40 ], PELI3 (interacts with complex containing IRAK kinases and TRAF6 of IL1 and TLR signaling pathways) [ 41 ], BST2 (Interferon induced anti-viral protein) [ 42 ], alarmins ( IL1A , IL36A and S100A9 ) [ 43 , 44 ], IRF1 (innate and adaptive immune response) [ 45 ], DEFB103A (antimicrobial peptide), CD207 (major receptor on langerhans cells for Candida species) [ 46 ], STAT2 (type 1 interferon signaling) [ 45 ] and MYD88 (adapter protein in Toll-like receptor signaling) [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table S1 lists the Top 50 differentially upregulated genes in OPM of VEH-untreated SIV rhesus macaques. Notable genes that were significantly upregulated exclusively in OPM of VEH-untreated/SIV rhesus macaques ( Figure 1 A) included IL1RN (inhibits activity of interleukin-1) [ 40 ], PELI3 (interacts with complex containing IRAK kinases and TRAF6 of IL1 and TLR signaling pathways) [ 41 ], BST2 (Interferon induced anti-viral protein) [ 42 ], alarmins ( IL1A , IL36A and S100A9 ) [ 43 , 44 ], IRF1 (innate and adaptive immune response) [ 45 ], DEFB103A (antimicrobial peptide), CD207 (major receptor on langerhans cells for Candida species) [ 46 ], STAT2 (type 1 interferon signaling) [ 45 ] and MYD88 (adapter protein in Toll-like receptor signaling) [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…IL6 then goes on to produce inflammatory cytokines in response to infections including tuberculosis in lung epithelial cells 40,41 . Heme oxygenase 1 (HMOX1) induces IL36RN expression, which acts as an IL36 antagonist to inhibit inflammation 49,50 . As shown in Figure 2c, MASL increased both HMOX1 and IL36RN mRNA expression in a dose responsive manner.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that IL-36R stimulates a signal transduction event through a mechanism that involves the actions of an adaptor protein myeloid differentiation primary response gene 88 (MyD88) and the interleukin-1 receptor associated kinase (IRAK) ( Figure 1 ) [ 32 , 33 , 34 ]. In addition, several known agonists (IL-36α, IL-36β, and IL-36γ) and antagonists (IL-36Ra, IL-38) have been shown to modulate its activity [ 22 , 35 , 36 ]. Signal transduction through this pathway leads to mitogen-activated protein kinase (MAPK) induced Activated Protein-1 (AP) and nuclear factor kappa-light-chain-enhancer of activated B cells (NF K B) dependent upregulation of pro-inflammatory gene expression ( Figure 1 ) [ 31 , 37 ].…”
Section: Molecular Basis and Biological Function Of Il-36r In Cellmentioning
confidence: 99%
“…IL-36R is highly expressed in the skin and epithelial cells, which are the major cell types involved in skin psoriasis [ 22 ]. According to the RNA-seq alignment reported by BioProject: (PRJEB4337), the human isoform of IL-36R is highly expressed in the esophagus, thyroid, kidney, skin, adrenal gland, and the gall bladder, yet the roles of IL-36R in these tissues are not fully defined [ 28 ].…”
Section: Molecular Basis and Biological Function Of Il-36r In Cellmentioning
confidence: 99%
See 1 more Smart Citation